(untitled) - Burke, James (Boston, 1978)
Contents: n this highly acclaimed and bestselling book, James Burke brilliantly examines the ideas, inventions, and coincidences that have culminated in the major technological advances of today. With dazzling insight, he untangles the pattern of interconnecting events: the accidents of time, circumstance, and place that gave rise to the major inventions of the world.
Keywords: Technology,Công nghệ; History,Lịch sử